Flavonols and flavonol glycosides in 21 black currant varieties - Ejaz, Huma (fi=Turun yliopisto|en=University of Turku|, 2018)
Flavonols are polyphenols from the class of flavonoids compounds known for their antioxidant, anti-cancerous and anti-inflammatory activities. Black currants belong to family Grossulariaceae having botanical name of Ribes nigrum. The concentrations of flavonols in black currants are affected by range of factors including plant variety, cultivation conditions and region, berry ripeness, harvesting conditions and time of the year, collection method and storage conditions. The aim of the thesis is to examine the impact of currant varieties on the flavonol content and composition of the black currant fruit. In this study the black currants were collected from 21 different varieties including nine from Scotland, five from Lithuania, one from Latvia, one from Poland, and five from Finland. Two green-colored varieties from Finland were also studied. Flavonol glycosides were extracted with ethyl acetate and were then analyzed with HPLC-DAD, to determine the different flavonols and flavonol glycosides in the sample. The most commonly found flavonols in the black currant samples were myricetin, quercetin and kaempferol. The flavonols were found mainly as glycosides. Myricetin mainly present as myricetin 3-O-glucoside, quercetin as quercetin 3-O-galactoside, and Kaempferol as kaempferol methoxyglucoside, Myricetin is the only flavonol found as glycoside as well as aglycone. The concentration of isorhamnetin found in trace amounts in all varieties. All varieties contain highest concentrations of myricetin 3-O-glucoside among flavonols except green-colored varieties, Venny and Vilma. The concentrations of different flavonols vary widely among varieties illustrating the importance of genetic background as a crucial factor. Due to high sample size variation it is difficult to understand the changes of flavonols contents among black currant varieties from different countries.